COMPUTER SKILLS OF LECTURERS, INSTITUTIONAL FACTORS, USEFULNESS AND USABILITY AS PREDICTORS OF LECTURERS' UTILISATION OF SCHOLARLY ELECTRONIC PUBLICATIONS INFEDERAL UNIVERSITIES IN NIGERIA (2013)
Developments in information and communication technology have resulted in the transformation of scholarly publications from paper to electronic medium. Previous studies have revealed that there was low level of utilisation of scholarly electronic publications (SEP) by lecturers in universities in Nigeria. Studies have also revealed that lecturers' computer skills, institutional factors (ICT infrastructure, academic workload, immediate work environment and staff training) usefulness (relevance) and usability (ease of use of SEP) are some of the factors that influenced utilisation of SEP among university lecturers in developed countries but not of those in developing countries like Nigeria. The study, therefore, investigated the combined effect of computer skills of lecturers, institutional factors, usefulness and usability on lecturers' utilisation of scholarly electronic publications in federal universities in Nigeria. The descriptive survey research design was used in the study. From a population of 6,168, a sample of 2,004 was drawn using accidental sampling technique. Data were collected through five questionnaires (computer skills of lecturers (r = 0.95); Institutional Factors (r = 0.79); usefulness (r = 0.85); usability (r = 0.93) and utilisation (r = 0.91)). This was complemented with observation checklist and interview schedule conducted on twenty-four lecturers in six universities. Seven research questions were answered and five hypotheses tested at 0.05 level of significance. Data were analysed with descriptive statistics, Pearson product moment correlation and multiple regression. The qualitative data were subjected to content analysis. Computer skills of lecturers (r=-.187, p < 0.05), Institutional factors (r = .06, p < .05) and usability correlated significantly with utilisation of SEP among lecturres while usefulness did not correlate significantly with utilisation of SEP. The combined effect of the independent variables determined utilization of SEP by lecturers in federal universities in Nigeria (F(4,139) = 22.865; R = .248, p < 0.05). Three independent variables made significant contributions namely, computer skills (? = .246, p < 0.05), institutional factors (? = 0.79, p < 0.05) and usability (? = .144, p < 0.05). Interview and observations revealed that lecturers possessed computer skills. It was observed that institutional factors such as ICT infrastructure and staff training were in place for lecturers to use SEP. The contents of SEP were useful for lecturers' researches and there was high level of usability. In addition, low level of utilisation of SEP was reported by lecturers. Computer skills of lecturers, institutional factors and usability combined are determinants of lecturers' utilisation of scholarly electronic publications in federal university libraries in Nigeria. Consequently, university managers should facilitate acquisition of relevant computer skills by lecturers. Also improvement in institutional factors and usability will lead to increased utilisation of scholarly electronic publications among lecturers.